PENGGUNAAN KARBON ARANG KAYU BELIAN DAN ARANG KAYU AKASIA PADA PROSES KARBURASI PADAT BAJA KARBON RENDAH - Fajar Setiawan, Bayu; Helanianto, Helanianto; Rahmadi, Hairian (Pengelola Jurnal Politeknik Negeri Ketapang, 2021)
Low carbon steel has a wide use in the construction sector and is classified into steel that can be processed by machinery (machinery steel). The salient disadvantage of this material is the type of failure in the form of chipping, and breaking. The purpose of this study was to determine the effect of the addition of belian and acacia wood charcoal on low carbon steel. This solid carburizing process uses a mixture of belian wood charcoal with calcium carbonate and acacia wood charcoal with calcium carbonate, and heattreatment at a temperature of 900oC, holding time of 30 minutes followed by quenching, with the Rockwell hardness test method. The test results show that the hardness of carbon steel that undergoes treatment is higher when compared to raw material of low carbon steel = 50.34HRB, where carburizing with acacia wood charcoal = 50.5HRB with a lower value when compared to belian wood charcoal = 50.94HRB. Judging from these results, the solid carburizing process with different types of charcoal will increase the hardness of low carbon steels.